Patterns of Extragenital Chlamydia and Gonorrhea in Women and Men Who Have Sex With Men Reporting a History of Receptive Anal Intercourse. Issue 2 (February 2016) - Danby, Claire S.; Cosentino, Lisa A.; Rabe, Lorna K.; Priest, Carol L.; Damare, Khrystine C.; Macio, Ingrid S.; Meyn, Leslie A.; Wiesenfeld, Harold C.; Hillier, Sharon L.
Abstract : Background: Screening for Chlamydia trachomatis ( CT ) and Neisseria gonorrhoeae ( GC ) in men who have sex with men is risk based. Despite high frequencies of oral and receptive anal intercourse (RAI) among women, extragenital screening is not recommended. Methods: Women (n = 175) and men who have sex with men (n = 224) primarily recruited from a sexually transmitted infection clinic reporting a lifetime history of RAI completed a structured questionnaire and clinician-collected swab samples from the rectum, pharynx, vagina (women), and urine (men). CT and GC were detected using 2 commercial nucleic acid amplification tests (Aptima Combo 2; Hologic, Inc, Bedford, MA; Xpert CT/NG, Cepheid Innovation, Sunnyvale, CA). Results: The median age of the population was 26 years, 62% were white, and 88% were enrolled from a sexually transmitted disease clinic. Men were more likely than women to have GC (22.8% vs. 3.4%) and CT (21.9% vs. 12.6%). In men versus women, GC was detected in 16.5% versus 2.3% of pharyngeal swabs, 11.6% versus 2.3% of rectal swabs, and 5.4% versus 2.9% of urine samples or vaginal swabs. C. trachomatis was detected in 2.2% versus 1.7% of pharyngeal swabs, 17.4% versus 11.4% of rectal swabs, and 4.5% versus 10.3% for urogenital sites in men versus women. Overall 79.6% of CT and 76.5% of GC in men and 18.2% of CT and 16.7% of GC in women were detected only in the pharynx or rectum. Conclusion: Reliance on urogenital screening alone misses most of GC and CT in men and more than 15% of infections in women reporting RAI. Abstract : Among people reporting a lifetime history of anal receptive intercourse, sexually transmitted infections are detected only at extragenital sites in up to 80% of men and 17% of women.